The relationship between institutional environment, guardian involvement, academic achievement and learning motivation of children reared in a Malaysian orphanage - Alfred, A. J.; Ma’rof, A. M.; Buang, N. (Pusat Pengkajian dan Penelitian Pendidikan Universitas Muhammadiyah Surakarta, 2017)
This research was conducted to study the relationships between academic performance, learning motivation, institutionalised environments and guardian involvement of children reared in a Malaysian orphanage. This study involves 50 students consisting of 21 female and 29 male students. These students are in secondary school with ages ranging from 13-17 years old. This study was conducted in a home for orphans and under-privileged children and all the participants of this study are from this home. The findings of this study show that there is a significant relationship between academic performance, intrinsic motivation, extrinsic motivation and therefore learning motivation as a whole (P<0.05). Findings also show that there is strong correlation between guardian involvement and academic performance (P<0.05). However for relationships between guardian involvement and learning motivation, institutionalised environment and academic performance and institutionalised environment and guardian involvement, correlations fail to exist (P>0.05).